The influence of learning interest and motivation on students’ achievementin learning physical education - Rajid, Rajid; Kahar, Irsan; Jalil, Rasyidah; Syahrir, Syahrir (Jurnal Porkes, 2023)
This study aimed to determine the influence of interest and learning motivation on physical education learning achievements of SMP Negeri 3 Walenrang students. This research used a quantitative descriptive method as outlined in the form of percentages. The population in this study were 171 students of SMP Negeri 3 Walenrang. The sample in this study was to 30 students. The results show that the highest interest in the sample with a percentage of 98.4% was in the very good category. Learning motivation has an average percentage of 88.6% describing that students' motivation to study physical education at SMP Negeri 3 Walenrang is very good. The high influence of learning interest of class VII students on physical learning achievement of SMP Negeri 3 Walenrang is obtained from a probability value of 0.00 (0.00 <0.05), then Ho's decision is rejected and H1 is accepted, meaning that there is a significant influence of learning interest on achievement learn penjas. While the motivation of VII Class students for physical education achievement at SMP Negeri 3 Walenrang is obtained from a probability value of 0.02 (0.00 <0.05), then Ho's decision is rejected and H1 is accepted, meaning that there is a significant influence of interest in learning on physical education achievement.